2018
DOI: 10.5812/aapm.79331
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein Level on Postoperative Day One is Associated with Chronic Postsurgical Pain After Mastectomy

Abstract: BackgroundC-reactive protein (CRP) is an acute phase reactant released in response to inflammation or tissue injury. Inflammation is one of the pathogenic factors related to transition from acute postsurgical pain (APSP) to chronic postsurgical pain (CPSP). Although several risk factors are reportedly associated with CPSP, the effects of CRP levels on CPSP have not been examined.ObjectivesThe present study investigated the relationship between perioperative risk factors, including CRP levels on postoperative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Studies exploring risk factors for CPSP in adults have emphasized the influence of the inflammatory response on postoperative pain. Immune cells and inflammatory molecules have been cited as a possible factors involved in the transition from acute to chronic postsurgical pain, 74 , 75 and circulating markers such as the neutrophil to lymphocyte ratio and C-reactive protein have been associated with CPSP 76 , 77 in adults. In the acute postsurgical literature, a single available pediatric study did not find a relationship between preoperative salivary cortisol concentrations and acute postoperative pain.…”
Section: Biological Factorsmentioning
confidence: 99%
“…Studies exploring risk factors for CPSP in adults have emphasized the influence of the inflammatory response on postoperative pain. Immune cells and inflammatory molecules have been cited as a possible factors involved in the transition from acute to chronic postsurgical pain, 74 , 75 and circulating markers such as the neutrophil to lymphocyte ratio and C-reactive protein have been associated with CPSP 76 , 77 in adults. In the acute postsurgical literature, a single available pediatric study did not find a relationship between preoperative salivary cortisol concentrations and acute postoperative pain.…”
Section: Biological Factorsmentioning
confidence: 99%
“…CRP is an acute‐phase reactant that reflects the response to inflammation or tissue damage. Recent studies showed that an increased level of postoperative CRP level was positively associated with increased acute postsurgical pain scores and analgesic requirement 21‐24 . CRP usually hits a peak level two or three days after surgery 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that an increased level of postoperative CRP level was positively associated with increased acute postsurgical pain scores and analgesic requirement. [21][22][23][24] CRP usually hits a peak level two or three days after surgery. 25 Contrary to the results of these studies, patients requiring rescue analgesia and the VAS scores in all assessment time points in ibuprofen treated patients were significantly lower than patients who received only IV paracetamol in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Плазмовий рівень СRP зростає пропорційно до ступеня пошкодження тканин [18] і є маркером розвитку та інтенсивності хронічного болю після мастектомії [19]. Підвищення плазмового рівня Среактивного білка через 24 і 72 год після операції зв'язано із післяопераційними ускладненнями [20].…”
Section: таблиця 3 біль за црш в першу добу після операції біль після операціїunclassified